2021
DOI: 10.1007/s11423-021-10009-4
|View full text |Cite
|
Sign up to set email alerts
|

Learning teamwork through a computer game: for the sake of performance or collaborative learning?

Abstract: Our study examined using a computer-based learning game as a tool to facilitate teaching and learning teamwork skills. The game was applied to an undergraduate level human resource management course at a business school in Finland. We focused on students’ experiences and key learning outcomes of collaborative learning of teamwork skills through the game, and our analysis highlighted two key features of learning outcomes. First, the computer-based learning game promoted students’ self-reflection and evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…The ENGAGE game as implemented in this study was observed to stimulate and maintain active participation among players throughout the gaming sessions. Increased active participation in the game experimental environment has also been reported in the literature (Jääskä and Aaltonen, 2022;Riivari et al, 2021;Speelman et 435 al., 2014b). Maintaining active participation among targeted stakeholders is key to promoting local solutions to complex catchment challenges (Lim et al, 2022;Stosch et al, 2022).…”
Section: Engagement Of Stakeholdersmentioning
confidence: 52%
“…The ENGAGE game as implemented in this study was observed to stimulate and maintain active participation among players throughout the gaming sessions. Increased active participation in the game experimental environment has also been reported in the literature (Jääskä and Aaltonen, 2022;Riivari et al, 2021;Speelman et 435 al., 2014b). Maintaining active participation among targeted stakeholders is key to promoting local solutions to complex catchment challenges (Lim et al, 2022;Stosch et al, 2022).…”
Section: Engagement Of Stakeholdersmentioning
confidence: 52%
“…Also, it has been highlighted that the VS found usually recreate situations that although are important for the student to understand and know how to proceed, it is difficult or even dangerous to have access to them for several reasons such as the complexity or impossibility of that situation to happen in real life (Falconer, 2013;Hannans et al, 2021;Menzel et al, 2014;Smith et al, 2016), the high risk for the subjects (patients, populations, etc) or even the own students (Aebersold, 2018; Keys et al, 2021;Rim & Shin, 2022), the huge responsibility that will imply for the learners (Buil et al, 2018;Holthaus & Longhi, 2022;Keys et al, 2021;Legner et al, 2013;Riivari et al, 2021;Rim & Shin, 2022;Tiffany & Hoglund, 2014;Verkuyl et al, 2020), or the need of other professionals or patients to be present to work interprofessional skills, leadership, teamwork, etc. (Espitia et al, 2021;Falconer, 2013;Lanzieri et al, 2020;Riivari et al, 2021;Rose et al, 2020;Sanborn et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the study with the participants, it was revealed how important it is for colleagues to engage in in-depth planning of the content they intend to teach and the class activities. These activities should not only align but also be engaging since empirical evidence supports this claim (Syakur & Sabat, 2020;Riivari et al, 2021;Imleesh et al, 2023). This construct is unique because only lecturers indicated proper planning as one of the factors that could sustain the adoption of collaborative learning in the university.…”
Section: Theme 2: Proper Planning As a Conditionmentioning
confidence: 99%